Failure analysis of AISI 420 steel turbine blade operating at low-pressure. (2022) - Sarim Khan, Mohd; Sasikumar, C
Abstract: In this paper failure of a low- pressure steam turbine blade is studied which failed prematurely after eight years of service. Here crack starts at the trailing edge and spreads towards the leading edge. Here it was observed brittle regions with multiple striations as well as multiple fast fracture regions indicating fatigue failure. At the crack initiation point, shallow corrosion pits were evident, but turbine vibrations caused crack initiation and propagation. Also, it was observed some deep pores with bright spots which were later found out be chromium oxides, which are later carried away by flowing steam leaving behind pores. There were shallow pits of corrosion at around crack initiation point. Vibrations in the turbine caused crack propagation. Also, at various locations lath martensite is also visible which also acts as a point of crack initiation. Thus, fluctuating loads increased in the turbine, causing fatigue cracks to form at potentially weaker areas, such as corrosion pits, which ultimately led to the turbine's failure.